The Emerging Roles of Extracellular Vesicles in Osteosarcoma - Perut, Francesca; Roncuzzi, Laura; Baldini, Nicola (Frontiers in Oncology, 2019)
Extracellular vesicles (EVs) are heterogeneous nanosized vesicles that are constitutively released by almost all cell types. They exist in virtually all body fluids and carry various molecules (proteins, lipids, metabolites, DNAs, and RNAs) on their surface as well as in the lumen. EVs confer stability and can direct their cargoes to specific cell types. They play a critical role in intercellular communication and cellular content transfer in both physiological and pathological settings. The extensive exploration of EVs improved our comprehension of cancer biology referring to tumor growth, metastasis, chemoresistance and treatment. In this review we describe the emerging data on the role of extracellular vesicles in osteosarcoma (OS) and discuss the effects and function of OS-derived EVs focusing on their future applicability in clinical practice.